Determinação dos compostos inorgânicos nitrogenados (amônia, nitrito e nitrato) e fósforo total, na água do açude Gavião, e sua contribuição para a eutrofização - Braga, Erika de Almeida Sampaio (2006)
The Gavião reservoir is located in the Pacatuba district of Ceará state (Lat:-3,904323ºS; Long:-38,528984ºW). The storage capacity of 53hm3, with hydraulic area of drainage basin and hydrographical basin 7 and 97 Km2, respectively. In spite of that Gavião reservoir is considered a model of reservoir and to constitute in the last reservoir of the system of the water supply of R.M.F., tends the downstream the Water Treatment Station ETA-Gavião, is being impactaded with anthropics activities. In the study was given attention to the inorganic compounds of nitrogenous, such as: ammonia, nitrite and nitrate and the phosphorus total, because them healthy very important nutrients to contributory for eutrophication in the consequence of the anthropics activities. For analyses of these parameters they were following the general guidelines of norms patterns for the methods of rehearsals, with the samples collected monthly, during the period of one year, of January of 2005 to December of 2005 and two periods were considered for the study, the humid period and the dry period. the conclusion with the study was arrived that the parameters concentrations investigate in the periods are more and more elevated, and consequently, degrading the water quality of the reservoir. When establishing the protection areas limits in turn of the sources of surface water, as well as the restrictions on the use of the soils that they accompany them, should feel a special attention to the activity types to be accomplished to amount of the reception area as well as to the quality of the natural water. Therefore, it is done necessary a control of the activities anthropics, through a more rigorous fiscalization, for the contribution of nutrients not to be one more responsible factor for the degradation of the quality of the water of Gavião reservoir, since this reservoir is the responsible for the water supply of the Metropolitan Area of Fortaleza.